Aethionema arabicum: a novel model plant to study the light control of seed germination. (5th April 2019) - Mérai, Zsuzsanna; Graeber, Kai; Wilhelmsson, Per; Ullrich, Kristian K; Arshad, Waheed; Grosche, Christopher; Tarkowská, Danuše; Turečková, Veronika; Strnad, Miroslav; Rensing, Stefan A; Leubner-Metzger, Gerhard; Mittelsten Scheid, Ortrun
Abstract : In contrast to the light requirement for Arabidopsis seed germination, the germination of several Aethionema arabicum accessions is inhibited by light, due to antipodal transcriptional regulation of hormone balance. Abstract: The timing of seed germination is crucial for seed plants and is coordinated by internal and external cues, reflecting adaptations to different habitats. Physiological and molecular studies with lettuce and Arabidopsis thaliana have documented a strict requirement for light to initiate germination and identified many receptors, signaling cascades, and hormonal control elements. In contrast, seed germination in several other plants is inhibited by light, but the molecular basis of this alternative response is unknown. We describe Aethionema arabicum (Brassicaceae) as a suitable model plant to investigate the mechanism of germination inhibition by light, as this species has accessions with natural variation between light-sensitive and light-neutral responses. Inhibition of germination occurs in red, blue, or far-red light and increases with light intensity and duration. Gibberellins and abscisic acid are involved in the control of germination, as in Arabidopsis, but transcriptome comparisons of light- and dark-exposed A. arabicum seeds revealed that, upon light exposure, the expression of genes for key regulators undergo converse changes, resulting in antipodal hormone regulation. These findings illustrate that similar modular components of a pathway in light-inhibited, light-neutral, and light-requiring germination among the Brassicaceae have been assembled in the course of evolution to produce divergent pathways, likely as adaptive traits.